(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Given this article that investigation of the degree of uniformity of the edge array during contour blasting. The stability of non-working quarry walls is affected by both the angle of inclination of the wall and the configuration of its slope. The effect of the slope configuration is to redistribute the rock volume of the collapse prism between the active pressure prism and the stop prism.